Data from: No place like home? A test of the natal habitat-biased dispersal hypothesis in Scandinavian wolves ... - Sanz Pérez, Ana; Ordiz, Andres; Sand, Håkan; Swenson, Jon; Wabakken, Petter; Wikenros, Camilla; Zimmermann, Barbara; Åkesson, Mikael; Milleret, Cyril (Dryad, 2018)
Natal dispersal is an important mechanism for the viability of populations. The influence of local conditions or experience gained in the natal habitat could improve fitness if dispersing individuals settle in an area with similar habitat characteristics. This process, defined as “natal habitat-biased dispersal” (NHBD), has been used to explain distribution patterns in large carnivores, but actual studies evaluating it are rare. We tested whether gray wolf Canis lupus territory establishment was influenced by the habitat characteristics of the natal territory using the long-term monitoring of the Scandinavian wolf population. We paired the locations of natal and established territories, accounted for available habitats along the dispersing route, and compared their habitat characteristics for 271 wolves during 1998-2012. Wolves with the shortest dispersal distances established in natal-like habitat types more than expected by chance, whereas wolves that dispersed longer distances did not show NHBD. The ... : Data_nhbdData allowing to reproduce the results of the conditional logistic regression to test the NHBD hypothesis. Each row correspond to an observation of a natal, established or available wolf territory. Variables describe the landscape characteristics of the territory, and the cluster/distance metric to which the territory was assigned in the different methods of defining habitat availability (i.e., clustering metods and distance metric). For further information on the variables refer to the README file attached to the excel document ...